2022
DOI: 10.21037/jtd-21-1824
|View full text |Cite
|
Sign up to set email alerts
|

A guide for managing patients with stage I NSCLC: deciding between lobectomy, segmentectomy, wedge, SBRT and ablation—part 2: systematic review of evidence regarding resection extent in generally healthy patients

Abstract: Background: Clinical decision-making for patients with stage I lung cancer is complex. It involves multiple options (lobectomy, segmentectomy, wedge, stereotactic body radiotherapy, thermal ablation), weighing multiple outcomes (e.g., short-, intermediate-, long-term) and multiple aspects of each (e.g., magnitude of a difference, the degree of confidence in the evidence, and the applicability to the patient and setting at hand).A structure is needed to summarize the relevant evidence for an individual patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 191 publications
1
7
0
1
Order By: Relevance
“…Reasonable speculation is that data from the recent Japan Clinical Oncology Group study (JCOG0802) (49) (a randomized controlled trial of segmentectomy vs. lobectomy for ≤2 cm tumors that are partially GG up to completely consolidated) may apply to a LCAL with a small solid component; The JCOG0802 study reported similar overall survival (OS) and recurrence-free survival (RFS) for lobectomy and segmentectomy. This is balanced against the general data for solid cI NSCLC that suggests survival is incrementally worse after lobectomy vs. segmentectomy vs. wedge vs. ablation (50,51). The high frequency of additional lung cancers suggests a need to balance management of the LCAL at hand with the ability to address future cancers.…”
Section: Definitive Treatment Recommendationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Reasonable speculation is that data from the recent Japan Clinical Oncology Group study (JCOG0802) (49) (a randomized controlled trial of segmentectomy vs. lobectomy for ≤2 cm tumors that are partially GG up to completely consolidated) may apply to a LCAL with a small solid component; The JCOG0802 study reported similar overall survival (OS) and recurrence-free survival (RFS) for lobectomy and segmentectomy. This is balanced against the general data for solid cI NSCLC that suggests survival is incrementally worse after lobectomy vs. segmentectomy vs. wedge vs. ablation (50,51). The high frequency of additional lung cancers suggests a need to balance management of the LCAL at hand with the ability to address future cancers.…”
Section: Definitive Treatment Recommendationsmentioning
confidence: 96%
“…We propose that segmentectomy may be best (if anatomically suitable) if intervention is undertaken at the first appearance of a solid component (based on infrequent node involvement and a propensity for additional lesions). We propose a pathologic margin of >1 cm be sought (extrapolating from traditional lung cancers) (50). For LCAL with more substantial solid components, we suggest a lobectomy is best (based on the high rate of node involvement and poor survival) (5,8).…”
Section: Definitive Treatment Recommendationsmentioning
confidence: 99%
“…They undertook this opus to create a practical guide for choosing the appropriate treatment strategy for individual patients based not only on the long-term and short-term outcomes, but also on the patient reported outcomes specific to each treatment strategy. This guide (1)(2)(3)(4) promotes a strategy that optimizes patient outcomes as well as patient satisfaction. In this way, we can select treatments that are both guideline concordant and goal concordant for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…Detterbeck et al have presented a comprehensive 4-part analysis and review of the literature supporting the various operative approaches (lobectomy, segmentectomy, wedge resection) and non-operative approaches for stage I nonsmall cell lung cancer (NSCLC) (1)(2)(3)(4). The literature search was focused over the last 21 years.…”
mentioning
confidence: 99%